The Basis is a Mobile Industrial Robot Core Characteristics and Shape of The Spatial Structure - N.R.Abdullayeva; A.K.Abdullayev (International Journal on Orange Technologies, 2021)
The geometric characteristics of the robot's work area - the size of the robot's work area, the cut surface, the linear, angular dimensions or a combination of them, the complexities of industrial robot movement are considered